The combination of Clostridium butyricum and Akkermansia muciniphila mitigates DSS-induced colitis and attenuates colitis-associated tumorigenesis by modulating gut microbiota and reducing CD8+ T cells in mice - Dengxiong Hua; Qin Yang; Xiaowei Li; Xuexue Zhou; Yingqian Kang; Yan Zhao; Daoyan Wu; Zhengrong Zhang; Boyan Li; Xinxin Wang; Xiaolan Qi; Zhenghong Chen; et al. (mSystems)
ABSTRACT The gut microbiota is closely associated with inflammatory bowel disease (IBD) and colorectal cancer (CRC). Probiotics such as Clostridium butyricum (CB) or Akkermansia muciniphila (AKK) have the potential to treat inflammatory bowel disease (IBD) or colorectal cancer (CRC). However, research on the combined therapeutic effects and immunomodulatory mechanisms of CB and AKK in treating IBD or CRC has never been studied. This study evaluates the potential of co-administration of CB and AKK in treating DSS/AOM-induced IBD and colitis-associated CRC. Our results indicate that compared to mono-administration, the co-administration of CB and AKK not only significantly alleviates symptoms such as weight loss, colon shortening, and increased Disease Activity Index in IBD mice but also regulates the gut microbiota composition and effectively suppresses colonic inflammatory responses. In the colitis-associated CRC mice model, a combination of CB and AKK significantly alleviates weight loss and markedly reduces inflammatory infiltration of macrophages and cytotoxic T lymphocytes (CTLs) in the colon, thereby regulating anti-tumor immunity and inhibiting the occurrence of inflammation-induced CRC. In addition, we found that the combined probiotic therapy of CB and AKK can enhance the sensitivity of colitis-associated CRC mice to the immune checkpoint inhibitor anti-mouse PD-L1 (aPD-L1), significantly improving the anti-tumor efficacy of immunotherapy and the survival rate of colitis-associated CRC mice. Furthermore, fecal microbiota transplantation therapy showed that transplanting feces from CRC mice treated with the co-administration of CB and AKK into other CRC mice alleviated the tumor loads in the colon and significantly extended their survival rate. Our study suggests that the combined use of two probiotics, CB and AKK, can not only alleviate chronic intestinal inflammation but also inhibit the progression to CRC. This may be a natural and relatively safe method to support the gut microbiota and enhance the host’s immunity against cancer.IMPORTANCEOur study suggests that the combined administration of CB and AKK probiotics, as opposed to a single probiotic strain, holds considerable promise in preventing the advancement of IBD to CRC. This synergistic effect is attributed to the ability of this probiotic combination to more effectively modulate the gut microbiota, curb inflammatory reactions, bolster the efficacy of immunotherapeutic approaches, and optimize treatment results via fecal microbiota transplantation.